Educating Student’s to Memorize the Qur’an Through School Extracurricular Programs - Yahya, Muhamad; Albizar, Albizar; Rahmi, Elvi; Fatimah, Fatimah; Hani, Umi; Vanessa, Anadya Diva (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2024)
Memorizing the Quran is one of the important aspects of Islamic education, and it not only functions as a means of building a love for the Quran but also forms a noble character in students. This study aims to analyze the school's planning, implementation, and evaluation of the tahfidz program. This study uses a qualitative method with a field research approach. Data were collected through interviews with tahfidz/tahsin teachers, students, principals, and coordinators of the Qur'an field. Data collection techniques include observation, documentation studies, and interviews, while data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions and verification. The results of the analysis show that the planning of the tahfidz program involves four main stages, namely the preparation of a syllabus that determines the material and surah to be memorized, determining the memorization target, preparing the LP (Lesson Plan), and a coordination meeting between Al-Qur'an teachers. The implementation of the tahfidz program in grade 4 follows four main steps, namely: i) iqomah, ii) tadkhil, iii) taqorir, and iv) closing in the form of motivation from the teacher and the recitation of the Kafaratul Majlis prayer. The results of the study indicate the importance of careful planning and periodic evaluation in maintaining the quality of student memorization. This program can be a model for other schools in compiling a structured and effective tahfidz program, especially at the elementary school level.